Education and the evolution of comparative advantage - Jesus Felipe; Hongyuan Jin; Aashish Mehta (Asian Development Bank (ADB), 2021)
We provide the first evidence that low- and middle-income countries with high education levels were more successful in developing comparative advantage in products unrelated to those they already export. In contrast, controlling for the relatedness of target products to these countries' exports, education appears unimportant for developing comparative advantage in products that are intrinsically complex or education intensive. These results are supported by analysis of the evolution of comparative advantage in 1,240 products from 49 low- and middle-income countries between 1995 and 2015. They are robust to corrections for measurement and specification errors, for institutional, infrastructure, and foreign direct investment-related factors, for regional specialization patterns, and for each economy's degree of industrial dynamism prior to 1995. These results suggest that the key role of education when seeking to shift from peripheral to core products is to help a country cope with unfamiliar challenges, and so overcome path dependence.
Keywords: I25; O11; O14; 330; comparative advantage; core; diversification; education; exports; path dependence; periphery; relatedness